Nilai Profetik Dalam Novel Bidadari Bermata Bening Karya Habiburrahman El Shirazy dan Implikasi terhadap Pembelajaran Sastra di Madrasah Aliyah - Palupi, Ratna (Aksara: Jurnal Bahasa dan Sastra, 2024)
This study aims to determine the prophetic values in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy and Implications for Literature Learning in Madrasah Aliyah (MA). In this thesis, researchers use analytical techniques or qualitative descriptive methods. Descriptive qualitative is qualitative data in the form of words, schemes, and images. The process of data analysis is carried out by reading, analyzing the prophetic values in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy. Based on data analysis, the results of analysis in the aspect of prophetic values were found through conversations and narratives in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy, it is known that there are 3 (three) elements of prophetic values in it, namely 1. Humanization (Amar Ma'ruf), 2. Liberation (Nahi Munkar), 3. Transcendence (Tu'minunna Billah). Researchers found 95 prophetic values in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy including (39 values of humanization or amar ma'ruf, 26 values of liberation or nahi munkar, 30 values of transcendence or tu'minunna billah). The results of this study revealed the prophetic values in the novel Bidadari Bermata Bening by Habiburrahman El Shirazy which narrowed down into three aspects. First humanization, humanization in this study is to produce far hatred, always do good to anyone who hurts, respect and respect parents, care for others and always invite in terms of kindness. Both liberations, liberation in this study is related to the rejection of corruption, eradication from ignorance, acquittal from vile accusations or slander, and discussion of the entanglement of use in political matters. Third, transcendence in this study is concerned with acknowledging God's power and power with complete conviction that everything and all motion and action proceeds from Him. Keywords: Prophetic Value, Qualitative Descriptive, Clear Eyed Angel Novel